Poranení pátere nastrelovacím hrebem - Kryl, J; Stulík, J; Vyskocil, T; Sebesta, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2006)
The patient, a 52-year-old male foreign citizen working as a construction worker, was attacked by his coworker who had fired a drive stud, 70 mm long, with reverse hooks from a powered gun at him; the stud pierced the worker's spine at the scapular level. The patient was taken to the nearest surgical ward. On the basis of clinical presentation and X-ray of the thoracic spine, the diagnosis of penetrating injury to the spinal column at the 7th thoracic vertebra level was made. Subsequently, the patient was admitted to the intensive care unit of our department. On admission the patients showed slight paresis of the right lower extremity and hypesthesia of the right thigh, but no other neurological deficit. After preoperative examination, the patient was operated on within six hours of the injury. Intraoperatively, a 3-mm-thick stud, piercing the T7 vertebral arch, was found on the left side, lateral to the T7 spinous process. After partial resection of the arch around the stud, the spinal canal was inspected. The stud passed paramedially on the right side through the dura mater and the centre of the spinal cord into the body of the 7th thoracic vertebra. The stud was gently removed. Subsequently, some sanguineous liquor appeared. The dura mater was sutured and the wound was closed layer by layer. The postoperative period was uneventful, and the patient was allowed to stand up on day 2. The drain was removed on day 4. Healing by first intention took place. At 6 weeks after surgery slight neurological deficit still remained. Key words: spinal penetrating injury, spinal gunshot injury.
Keywords: Spinal Injuries; cizí tělesa; penetrující rány; lidé; Foreign Bodies; Wounds, Penetrating; poranění páteře; Humans; Male; mužské pohlaví; Middle Aged; lidé středního věku